CLINICAL AND FUNCTIONAL SUBSTANTIATION OF FORMING OF “NEORECTUM” WITH USE OF ILEOASCENDOCECAL COMPLEX - V. V. Yanovoy; S. V. Anikin; A. A. Simonenko (Acta Biomedica Scientifica, 2012)
Clinical and functional results of the "low" resection with foring of "neorectum" by ileoascendocecal complex tmnsposition and reveron were studied, in 32 patients. It was shown that this method, permits to get good functional results and. to prevent "low anterior resection syndrome" development.